2021
DOI: 10.5541/ijot.878173
|View full text |Cite
|
Sign up to set email alerts
|

On the Allocation of Residues Cost using Conventional and Comprehensive Thermoeconomic Diagrams

Abstract: In a productive process, the achievement of products occurs simultaneously with residues generation. Environmental impact of residues is an important issue in energy systems analysis due to environmental regulations and sustainability assessment. Many waste treatment methodologies have been proposed and applied in thermoeconomics. However, this is a complex problem and the solution depends on the residue nature and its formation process. Most conventional methodologies are based on productive diagrams, using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…In the H&S Model, the productive flows represent variations of the enthalpic, entropic and chemical components of the exergy between i and j according to Eqs. ( 8) - (10), respectively.…”
Section: Productive Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…In the H&S Model, the productive flows represent variations of the enthalpic, entropic and chemical components of the exergy between i and j according to Eqs. ( 8) - (10), respectively.…”
Section: Productive Diagrammentioning
confidence: 99%
“…In these circumstances, thermoeconomics allows rational allocation (through physical criteria) of monetary, exergetic, and environmental costs for the final products. Therefore, it is possible to compare exergetic/monetary [10][11][12][13][14] and/or environmental [15][16][17][18] costs of each product with the production cost of each one in separate systems. Thermoeconomic methodologies have already been used to include environmental aspects, such as specific CO2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In such scenarios, thermoeconomics enables a rational allocation (based on physical criteria) of monetary, exergetic, and environmental costs for these final products. Consequently, a comparison becomes feasible between the exergetic/monetary/environmental costs of each product and the production cost of each individual product in separate systems, as shown in papers assessing the exergetic unit cost (in a regenerative gas turbine cogeneration system [13]; in a cogeneration system with gas turbine, intercooler, and supplementary firing [14]; and in a combined cycle [15]), monetary unit cost (in a gas turbine cogeneration system [16] and in a power generation system of a steel mill plant [17]), and emissions pollutant allocation (in gas and steam cogeneration systems [18], in a gas cogeneration system with supplementary firing [19], in a combined cycle [20], and in a dual product heat pump [21]). Despite the practical relevance of this aspect, in the literature review, no studies were found that dealt with the incorporation and internalization of the monetary unit cost linked to the carbon market in the thermoeconomic evaluations of multi-product plants.…”
Section: Introductionmentioning
confidence: 99%